Extraction, Characterization, and Applications of Pectins from Plant By-Products - Anissa Belkheiri; Ali Forouhar; Alina Violeta Ursu; Pascal Dubessay; Guillaume Pierre; Cedric Delattre; Gholamreza Djelveh; Slim Abdelkafi; Nasser Hamdami; Philippe Michaud (Applied Sciences, 2021)
Currently, pectins are widely used in the cosmetic, pharmaceutical, and food industries, mainly as texturizing, emulsifying, stabilizing, and gelling agents. Pectins are polysaccharides composed of a large linear segment of α-(1,4) linked d-galactopyranosyluronic acids interrupted by β-(1,2)-linked l-rhamnoses and ramified by short chains composed of neutral hexoses and pentoses. The characteristics and applications of pectins are strongly influenced by their structures depending on plant species and tissues but also extraction methods. The aim of this review is therefore to highlight the structures of pectins and the various methods used to extract them, including conventional ones but also microwave heating, ultrasonic treatment, and dielectric barrier discharge techniques, assessing physico-chemical parameters which have significant effects on pectin characteristics and applications as techno-functional and bioactive agents.